Interactive evaluation of the main agrotechnical factors in rape production - Kátai, Zoltán (Acta Agraria Debreceniensis, 2009)
Our polifactorial rape research was carried out at Látókép Research Centre of Debreceni Egyetem AMTC, 15 km away from Debrecen. The aim was to study the unique effect and the interactive effect of more factors. The research factors were the following: cultivation, time of sowing and nutrient supply. Soil moisture datas proved unambiguously that increasing amounts of chemical fertilizer raise the water consumption of rape, lack of water in fertilized plots were always bigger then the water deficit in control plots. The highest amount of water deficit was experienced in the case of arable plots. However, increasing amounts of chemical fertilizers raised the amount of yield proportionately. We experienced yield depression only in the case of arable plots at the highest level of chemical fertilization. In polifactorial rape research sowing of 24th August 2007 of 2007/2008 was the most optimal in point of the amount of yield. This is most-significant in the case of loosening tillage and disking tillage plots, while the plots of ploughing lag behind those two in point of average yield. We experienced the biggest differences of yield in the case of different tillage plots of sowing on 24t August 2007. Still not even the plot with the highest average reached the limit of 4 tons, which can be attributed to high rate of lodging and the harvest loss caused by this. The biggest amount of yield was experienced in the case of sowing of 24th August 2007, with the highest level of chemical fertilization at loosening tillage plot (3930 kg/ha). We can observe big differences between the tillage methods; plots of loosening show a much better average yield then plots of disking and ploughing tillage. Considering the first observed crop year we can state that alternative tillage methods do have a future in rape growing of Hungary.